Technical Digest. Summaries of Papers Presented at the Quantum Electronics and Laser Science Conference. Postconference Technic
DOI: 10.1109/qels.2001.962056
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of carrier-wave Rabi flopping in GaAs

Abstract: For excitation of the model semiconductor GaAs with optical pulses which are both extremely short (5 fs) and extremely intense (ഠ10 12 W cm 22 ), we can meet the condition that the Rabi frequency becomes comparable to the band gap frequency -a highly unusual and previously inaccessible situation. Specifically, in this regime, we observe carrier-wave Rabi flopping, a novel effect of nonlinear optics which has been predicted theoretically and which is related to the failure of the area theorem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…Ziolkowski et al found that the time-derivative behavior of the carry-wave field has a significant impact on the time evolution of a two-level atom system [11]. Moreover, for large pulse areas (>10π), the phenomenon of the carrier-wave Rabi flopping (CWRF) can lead to carrier-wave reshaping and significantly higher spectral components and even soft x-ray generation was proposed by Hughes [12], and it then was proved in experiment [13]. Furthermore, Xiao et al reported that, contrary to the long-pulse, the variation of the fewcycle pulse area is caused by the pulse splitting and not by pulse broadening or compression [17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ziolkowski et al found that the time-derivative behavior of the carry-wave field has a significant impact on the time evolution of a two-level atom system [11]. Moreover, for large pulse areas (>10π), the phenomenon of the carrier-wave Rabi flopping (CWRF) can lead to carrier-wave reshaping and significantly higher spectral components and even soft x-ray generation was proposed by Hughes [12], and it then was proved in experiment [13]. Furthermore, Xiao et al reported that, contrary to the long-pulse, the variation of the fewcycle pulse area is caused by the pulse splitting and not by pulse broadening or compression [17].…”
Section: Introductionmentioning
confidence: 99%
“…For long pulse, we can use the Maxwell-Bloch (M-B) equations with the slowly varying envelop approximation (SVEA) and the rotating-wave approximation (RWA) to obtain some important results, for example, the area theorem [9,10], which can predict and explain many interesting phenomena such as self-induced transparency (SIT) and pulse compression. However, for few-cycle laser pulse, these approaches fail clearly [11][12][13][14]. Using the full M-B equations without SVEA and RWA, the propagating behaviors of few-cycle laser pulse in two-level atomic or molecular mediums have been investigated in many literatures [1][2][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…were first experimentally observed by Mücke et al [187] on the interband transition of GaAs. The authors identify the CW regime by the appearance of higher harmonics in the spectrum of the emitted signal.…”
Section: Rabi Oscillations In the Carrier Wave Regimementioning
confidence: 89%
“…Sub-cycle optical waveforms would allow to steer, switch and control such wave packets, enabling radically new implementations of electron diffraction and electron microscopy [27] with unprecedented combination of spatial and temporal resolution. Sub-cycle optical waveforms also find applications in the study of strong-field light-matter interactions in solids [28]- [37] and for the control of electric currents in (and thereby emitted HHG from) semiconductors [38], [39] and insulators on the sub-cycle timescale. Such extreme interactions of short optical waveforms with solids are expected to enable the field of lightwave nanoelectronics, which is based on nanocircuits, which accept data as light in the form of plasmons.…”
Section: Introductionmentioning
confidence: 99%